analisis penentuan wilayah Blackspot terjadinya kecelakaan lalu lintas di jalan soekarno-hatta lampung - Ferdian, Yuda Ariza; Sulistyorini, Rahayu; Karami, Muhammad (Universitas Lampung, 2019)
Traffic accidents need to get greater attention. Road accidents always have an impact on damage and losses for vehicles involved in accidents and road users around them. The cause of traffic accidents is due to unfavorable traffic conditions. The condition is divided into 4 factors which include human factors, vehicle factors, environmental factors and road factors.The accident data used in this study are secondary data obtained from the Bandar Lampung Police Department in 2015 to 2017. The methods used are Frequency Method, Highways Weighting Method, INDII-Aus Aid Weighting Method and KSI Method. The purpose of this study is to find out the Blackspot Region which often occurs in traffic accidents, knowing the causes that influence and prevention so that the level of accidents that occur can be anticipated and how to overcome the Blackspot Region.Based on the results of calculations obtained from the Frequency Method, Weighting of Highways, Weighting of INDII-Aud Aid and KSI, in 2017 7 Blackspot Areas were obtained. In 2016 only used the Frequency Method obtained by 6 Blackspot Areas.Whereas in 2015 also only used the Method of Frequency obtained by 5 Blackspot Areas.Keywords: Black Spot, Frequency Method, Highways Weighting Method, INDII-Aud Aid Weighting Method, KSI Method